2019
DOI: 10.6000/2292-2598.2019.07.04.1
|View full text |Cite
|
Sign up to set email alerts
|

Premutation Allele Combined with Caregiver Distress Factor Increase the Risk of Depression in Fragile X Carriers: Indonesia Setting

Abstract: This study was done to determine the risk of anxiety and depression symptoms among fragile X premutation carriers. Hamilton anxiety rating scale (HARS) and Hamilton depression rating scale (HDRS) was administered by trained physicians to measure the severity of anxiety and depression symptoms, respectively. Caregiver distress factors which directly contribute to caregiver burden in particular degree of relationship with the child, number of FXS child, child institutional/educational status, number of hours spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Moreover, PM carrier women were at significantly increased risks for various neuropsychiatric features such as anxiety, sleep disturbances, aggression, difficulty in concentrating, hyperreactivity and language issues than non-PM carrier women as these features were present at high frequencies in PM carriers in this study. Previous studies have also reported significantly higher rates of sleep disturbances [ 52 , 53 ], depression, stress and anxiety [ 31 , 54 ], language issues [ 16 , 55 ], attention deficits [ 16 , 48 ], and memory impairment [ 56 , 57 ] in PM carriers with or without diagnosis of Fragile X associated disorders compared with controls. Hartley et al [ 58 ] in a study noted predominantly aggression, inattentive, behavior problems and irritability, whereas Chonchaiya et al [ 59 ] observed high prevalence of balance problem, memory loss, dizziness among PM carriers with history of FXD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PM carrier women were at significantly increased risks for various neuropsychiatric features such as anxiety, sleep disturbances, aggression, difficulty in concentrating, hyperreactivity and language issues than non-PM carrier women as these features were present at high frequencies in PM carriers in this study. Previous studies have also reported significantly higher rates of sleep disturbances [ 52 , 53 ], depression, stress and anxiety [ 31 , 54 ], language issues [ 16 , 55 ], attention deficits [ 16 , 48 ], and memory impairment [ 56 , 57 ] in PM carriers with or without diagnosis of Fragile X associated disorders compared with controls. Hartley et al [ 58 ] in a study noted predominantly aggression, inattentive, behavior problems and irritability, whereas Chonchaiya et al [ 59 ] observed high prevalence of balance problem, memory loss, dizziness among PM carriers with history of FXD.…”
Section: Discussionmentioning
confidence: 99%
“…Management of individuals with FXS-associated disorders comprises long-term health supervision, starting from a young age through adulthood. In addition, to identifying those with FMR1 premutation-associated disorders such as Fragile-X associated tremor/ataxia syndrome (FXTAS) at a later age, Fragile-X associated primary ovarian insufficiency (FXPOI) among female carriers and the risk of having fragile X-associated neuropsychiatric disorders (FXAND) at all ages (26,27). To date, in Indonesia, there are no specific clinical guidelines or recommendations regarding individuals with FXS, premutation disorders or ID in general.…”
Section: Management Of Fxs In Indonesiamentioning
confidence: 99%